Survival motor neuron gene 2 silencing by DNA methylation correlates with spinal muscular atrophy disease severity and can be bypassed by histone deacetylase inhibition - Hauke, Jan; Riessland, Markus; Lunke, Sebastian; Eyüpoglu, Ilker Y.; Blümcke, Ingmar; El-Osta, Assam; Wirth, Brunhilde; Hahnen, Eric (Human molecular genetics, 2009)
Spinal muscular atrophy (SMA), a common neuromuscular disorder, is caused by homozygous absence of the survival motor neuron gene 1 (SMN1), while the disease severity is mainly influenced by the number of SMN2 gene copies. This correlation is not absolute, suggesting the existence of yet unknown factors modulating disease progression. We demonstrate that the SMN2 gene is subject to gene silencing by DNA methylation. SMN2 contains four CpG islands which present highly conserved methylation patterns and little interindividual variations in SMN1-deleted SMA patients. The comprehensive analysis of SMN2 methylation in patients suffering from severe versus mild SMA carrying identical SMN2 copy numbers revealed a correlation of CpG methylation at the positions −290 and −296 with the disease severity and the activity of the first transcriptional start site of SMN2 at position −296. These results provide first evidence that SMN2 alleles are functionally not equivalent due to differences in DNA methylation. We demonstrate that the methyl-CpG-binding protein 2, a transcriptional repressor, binds to the critical SMN2 promoter region in a methylation-dependent manner. However, inhibition of SMN2 gene silencing conferred by DNA methylation might represent a promising strategy for pharmacologic SMA therapy. We identified histone deacetylase (HDAC) inhibitors including vorinostat and romidepsin which are able to bypass SMN2 gene silencing by DNA methylation, while others such as valproic acid and phenylbutyrate do not, due to HDAC isoenzyme specificities. These findings indicate that DNA methylation is functionally important regarding SMA disease progression and pharmacological SMN2 gene activation which might have implications for future SMA therapy regimens.